Infra-red thermography estimate of deposited heat load dynamics on the lower tungsten divertor of WEST. (6th March 2020) - Fedorczak, N; Gaspar, J; Firdaouss, M; Moncada, V; Grosjean, A; Dejarnac, R; Brezinsek, S; Tsitrone, E; Bucalossi, J; Loarer, T
Abstract: A thermography inversion algorithm (TEDDY) was developed for the physical exploitation of WEST infra-red thermography (at 3.9 μ m) of uncooled graphite tiles coated with 12 μ m of tungsten, located at the lower divertor. The numerical scheme features a conservative finite volume approach with the full temperature non linearity of thermal properties of material composing the tile. The inversion algorithm is validated against synthetic test cases built from standardized software. A first in situ quantification of tungsten surface emissivity and reflected luminance along an outer target coated tile is then detailed. This method relies on a comparison of thermography data with absolute temperature measurements from embedded thermal sensors. Low surface emissivity ( ϵ ≈ 0.05) is estimated in the common outer strike point area, while increasing to about 0.1–0.15 far from it, possibly due to deposited impurity layers. The heat flux inversion from corrected thermography temperature is illustrated on an L-mode plasma heated with 4 MW of input power, featuring a strike point sweeping of 30 mm along the divertor tile. Power balance and sweeping dynamics are consistently recovered by the heat flux inversion, while the radial profile of parallel heat flux remapped to outer midplane features a Gaussian-exponential shape common to diverted configurations in low dissipation divertor regime.